Karakteristik Kualitas Daging Sapi Peranakan Ongole yang Berasal dari Otot Longissimus Dorsi dan Gastrocnemius - Nuraini, Nuraini; Hafid, Harapin (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2006)
TheÂ researchÂ targetÂ wasÂ toÂ knowÂ Â Â theÂ characteristicÂ ofÂ beefÂ qualityÂ ofÂ Peranakan OngoleÂ cattleÂ withÂ meatÂ sampleÂ fromÂ LongissimusÂ dorsiÂ andÂ Gastrocnemius.Â DataÂ of tenderness and characteristic of chemical composition of beef using t-Student test. Result of research indicated that the musculus Longissimus dorsi is more tender than musculus Gastrocnemius.Â FatÂ contentÂ ofÂ musculusÂ Longissimus dorsiÂ wasÂ higherÂ thanÂ thatÂ of musculus Gastrocnemius. On the other hand, water, crude protein and mineral content of musculus Longissimus dorsi was lower than those of musculus Gastrocnemius.Â